1992
DOI: 10.1111/j.1600-0447.1992.tb03315.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Antabuse treatment: tolerance and reasons for withdrawal

Abstract: term Antabuse treatment: tolerance and reasons for withdrawal. Acta Psychiatr Scand 1992: 86: 47-49.Abstract -We studied 210 alcoholics, who were re-admitted to a disulfiram treatment programme after having voluntarily discontinued disulfiram therapy, primarily to ascertain whether illness, hospitalization, or serious adverse effects were the cause of the withdrawal. A simple 9-item questionnaire was used. About 70 'To of the patients gave either "a wish to drink again" or "no need for further treatment" as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…Disulfiram not only enhanced the antitumor efficacy of g-radiation delivered from an external source but also potentiated the efficacy of 131 I-MIBG targeted radionuclide therapy, in both spheroid and xenograft models. Significantly, the synergistic activity in vivo was achieved at a disulfiram dosage that had negligible effect on xenograft tumor growth and has previously been demonstrated to be associated with insignificant side effects (9). Such features are highly desirable in a radiosensitizing agent.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Disulfiram not only enhanced the antitumor efficacy of g-radiation delivered from an external source but also potentiated the efficacy of 131 I-MIBG targeted radionuclide therapy, in both spheroid and xenograft models. Significantly, the synergistic activity in vivo was achieved at a disulfiram dosage that had negligible effect on xenograft tumor growth and has previously been demonstrated to be associated with insignificant side effects (9). Such features are highly desirable in a radiosensitizing agent.…”
Section: Resultsmentioning
confidence: 83%
“…These include the induction of oxidative stress (2,3), the generation of copper-dependent toxicity (2,4), proteasome inhibition (4-6), and nuclear factor-kB inhibition (7,8). Despite its diverse range of pharmacologic activities, prolonged treatment with disulfiram has negligible, reversible, adverse effects and is considered a safe drug (9). Disulfiram is currently undergoing clinical trials for the treatment of various cancers including melanoma and liver, lung, and prostate.…”
mentioning
confidence: 99%
“…S1A, S2B, and S3). From these candidate compounds, we chose montelukast, a leukotriene receptor antagonist used for the treatment of acute asthma (36,37), clioquinol, a hydroxyquinoline that has been used as an antifungal and antiprotozoal drug (38), and disulfiram, an off-patent drug previously used to treat alcoholism (21,39) for further assessment. While in vitro studies were validated for clioquinol ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As DSF has been used clinically for over 60 years to treat alcoholism, its pharmacokinetics has been extensively studied and shown to have an excellent safety record at FDArecommended doses (20,21). DSF is available, inexpensive, safe, and overall well-tolerated making it an attractive candidate for "repurposing" in the context of glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are other studies that add weight to the evidence that disulfiram is not a drug with high incidence of adverse effects [6]. Larson FW et al (1992) reported that in treatment of alcohol dependence, disulfiram is most useful in conjuction with a structured, supervised, aftercare program [7].…”
mentioning
confidence: 99%